2021
DOI: 10.1177/17470218211057466
|View full text |Cite
|
Sign up to set email alerts
|

Temporal grouping effects in verbal and musical short-term memory: Is serial order representation domain-general?

Abstract: The question of the domain-general versus domain-specific nature of the serial order mechanisms involved in short-term memory is currently under debate. The present study aimed at addressing this question through the study of temporal grouping effects in short-term memory tasks with musical material, a domain which has received little interest so far. The goal was to determine whether positional coding—currently the best account of grouping effect in verbal short-term memory—represents a viable mechanism to ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(223 reference statements)
1
0
0
Order By: Relevance
“…In the present study, the impaired serial-order STM of DYS+A children was expressed independently of material (i.e., for words, pitches, and timbre), as revealed by the absence of interaction with this variable. This may support the argument that serial-order STM is governed by common processes in the verbal and musical domains, in line with previous studies that have shown similar hallmarks of serial-order effects in verbal and musical STM (Gorin et al, 2018; see also Gorin, 2021;Williamson, Baddeley, et al, 2010). One proposal is that music and language serial-order processing possibly rely on common sequential processes.…”
Section: Implications For Theoretical Models Of Stmsupporting
confidence: 90%
“…In the present study, the impaired serial-order STM of DYS+A children was expressed independently of material (i.e., for words, pitches, and timbre), as revealed by the absence of interaction with this variable. This may support the argument that serial-order STM is governed by common processes in the verbal and musical domains, in line with previous studies that have shown similar hallmarks of serial-order effects in verbal and musical STM (Gorin et al, 2018; see also Gorin, 2021;Williamson, Baddeley, et al, 2010). One proposal is that music and language serial-order processing possibly rely on common sequential processes.…”
Section: Implications For Theoretical Models Of Stmsupporting
confidence: 90%